The Comparative Effects of Recombinant Hirudin (CGP 39393) and Standard Heparin on Thrombus Growth in Rabbits - Agnelli, Giancarlo; Pascucci, Claudia; Cosmi, Benilde; Nenci, Giuseppe G (Thrombosis and Haemostasis, 1990)
The aim of this study was to compare the ability of standard heparin and recombinant (r-)hirudin, a specific inhibitor of thrombin, to inhibit thrombus growth in a rabbit jugular vein model. Doses of standard heparin and r-hirudin equivalent in prolonging the aPTT were first identified. The ability of these doses to inhibit 125I-fibrin accretion onto preexisting thrombi was then evaluated. 0.5 and 0.75 mg/kg of standard heparin and 0.8 and 1.25 mg/kg of r-hirudin infused over 3 h produced a mean prolongation of the aPTT of 1.5 and 2 times, respectively. In saline treated rabbits 62 ± 7 μg of 125I-fibrin were accreted on the pre-formed thrombi. The lower doses of standard heparin and r-hirudin produced a 125I-fibrin accretion of 44 ± 5 and 25 ± 4 μg, respectively (p <0.01). The two higher doses of standard heparin and r-hirudin produced a 125I-fibrin accretion of 34 ± 4 and 17 ± 3 μg, respectively (p <0.01). The increase in the dose of standard heparin up to 2.5 mg/kg produced a 125I-fibrin accretion of 26 ± 3 μg, a 58% reduction when compared with saline. The increase in the dose of r-hirudin up to 5 mg/kg produced a 125I-fibrin accretion of 12 ± 2 μg, an 81% reduction when compared with saline. No further inhibition was observed when the doses of both agents were further increased. We conclude that doses of standard heparin and r-hirudin equivalent in prolonging the aPTT have a different effect on thrombus growth inhibition, r-hirudin being twice as effective as standard heparin. Exclusive inhibition of thrombin without any other inhibiting effect on blood coagulation appears to be sufficient to inhibit thrombus growth. Our results seem to be promising in view of a clinical evaluation of r-hirudin